Study on Fatigue Characteristics of Carbonation Erosion Prestressed Hollow Slabs in Whole Life Cycle - Yuanxun Zheng; Kuan Li; Mengen Ji; Ehsan Moshtagh (Advances in Civil Engineering)
In this paper, the whole life cycle (failure-reinforcement-failure) durability and related fatigue properties of prestressed hollow beam under carbonation erosion environment were studied. According to a 20 m hollow slab beam, the model of prestressed hollow beam was designed and made, and the durability and fatigue tests for the whole life cycle of prestressed hollow beam were carried out. The results showed that the compressive strength and elastic modulus of the specimens increased by about 20% under the action of carbonization erosion. With the increase of fatigue loading cycles, the crack occurrence and development speed of carbonized erosion components were greater than those of healthy components, and the fatigue life decreased sharply from 3 million cycles to 50,000 cycles. Pasting carbon fiber and steel plate had better reinforcement effect on the damaged prestressed plate beam and could help improving the fatigue life of the reinforced component. Comparing the reinforcement of different strengthening methods, it is found that the steel-plate-reinforced components have better mechanical properties and antifatigue attenuation characteristics than the carbon-fiber-reinforced ones. The research results have important theoretical value for improving the durability of structure and prolonging its service life.